Teacher Education: Design Thinking Approach in Makerspaces to Produce Quality Educational Video Games with a Visual Identity and Improve Design Thinking Skills - Yara Ahmed Mohebeldin Zaky; Ensaf Nasser Al Mulhim (MDPI AG, 2024)
Video games participate effectively in the educational process due to their attractive visual features, but there are many challenges that teachers face when using them. Among these challenges is designing games to suit the goals of the educational process and respecting societal identity. Although there are many studies on educational video games, limited approaches that enhance teachers' education have been explored. The current study focuses on stimulating pre-service teachers' design thinking skills and improving the quality of their video games that have a visual identity by incorporating a design thinking approach into a makerspace. This study followed a quasi-experimental approach, in which 38 pre-service teachers from the departments of Art Education, Early Childhood Education, and Educational Technology at the College of Education at King Faisal University in Saudi Arabia participated. They designed and produced educational video games that consider visual identity and completed the design thinking scale. The results showed that there was great cooperation between participants from all disciplines in the work team, which affected the generation of creative and innovative ideas and the quality of the educational video games. This is due to the use of design thinking elements such as empathy, identification, ideation, and prototyping with different tools in the makerspace. This study calls for the use of a design thinking approach in the classroom learning space for teachers' education, discusses implications for educational practices, and recommends further research in this area.